Application of the hierarchical model of intrinsic and extrinsic motivation in the context of exercise: a systematic review - Viveiros, Bernardo; Jacinto, Miguel; Antunes, Raúl; Matos, Rui; Amaro, Nuno; Cid, Luís; Couto, Nuno; Monteiro, Diogo (Frontiers in Psychology, 2025)
Given the increase in sedentary lifestyles and physical inactivity, various psychosocial approaches have been used to combat this epidemic. Several studies have used Self-Determination Theory (SDT) as a theoretical framework for studying behavioral change, as well as the Hierarchical Model of Intrinsic and Extrinsic Motivation (HMIEM) which, based on SDT, aims to explain how different levels of generality can be responsible for behavioral consequences. The aim was to investigate the associations between the variables that make up the HMIEM model applied to the context of physical exercise (gym exercisers). Following the PRISMA protocol and the PECOS strategy, the Web of Science, PubMed, Scopus, and SPORTDiscus databases were used to search for experimental and non-experimental studies written in English. Seven studies were considered for analysis and subjected to a methodological quality assessment The results showed that the variables that make up the social factors (e.g., supportive/thwarting behaviors) tend to be associated with satisfaction of basic psychological needs (BPN) (r = 0.51, p < 0.01; r = −0.73, p < 0.01) and with frustration of BPN (r = −0.39, p < 0.01; r = 0.78, p < 0. 01), BPN satisfaction and frustration tend to be associated with autonomous forms of motivation (r = 0.57, p < 0.01; r = −0.63, p < 0.01) and controlled forms of motivation (r = −0.76, p < 0.01; r = 0.46, p < 0.01) and autonomous and controlled forms of motivation are associated with behavioral consequences (e.g., intention) (r = 0.19, p < 0.01; r = −0.17, p < 0.01). This systematic review covers interpersonal behaviors and the bright and dark sides of SDT, showing that the positive alignment between the psychosocial determinants that make up the horizontal axis of the HMIEM is fundamental for adherence to and maintenance of sustainable physical exercise practices, and future studies should now address these issues in a longitudinal manner and perhaps move on to study the vertical axis of the HMIEM.